Spatio‐temporal assessment of the hydrological drivers of an active deep‐seated gravitational slope deformation: The Vögelsberg landslide in Tyrol (Austria). Issue 10 (13th May 2021) - Pfeiffer, Jan; Zieher, Thomas; Schmieder, Jan; Rutzinger, Martin; Strasser, Ulrich
Summary: Spatio‐temporal variations of precipitation are presumed to influence the displacement rate of slow‐moving deep‐seated landslides by controlling groundwater recharge, pore‐water pressure and shear strength. Phases of landslide acceleration responding to long‐lasting rainfall and snowmelt events occur under site‐ and event‐specific time delays. Assessing groundwater recharge and simultaneous recording of landslide displacement in a sufficient spatial and temporal resolution is essential to deepen the understanding of mechanisms controlling a landslide's deformation behaviour and is indispensable when it comes to identifying and developing target‐oriented mitigation strategies. The objective of this study was to assess hydrological landslide drivers (solid and liquid precipitation, snowmelt and evapotranspiration) and to investigate their spatio‐temporal distribution in the context of movements recorded at the Vögelsberg landslide (Tyrol, Austria). Hydrometeorological variables were simulated using the AMUNDSEN (Alpine MUltiscale Numerical Distributed Simulation ENgine) hydroclimatological model and landslide movements were continuously monitored using an automated tracking total station. Area‐wide simulated time series of available water were used: (i) to separate them into single landslide triggering hydrometeorological events; (ii) to analyse spatio‐temporal patterns of water availability per triggering event including individual response times; (iii) to delineate an effective hydrological landslide catchment; and (iv) to identify relations between assessed water input and landslide displacement rate. For the observation period from 05‐2016 until 06‐2019 we identified three distinctive hydrometeorological events causing time‐delayed periods of landslide acceleration. Spatio‐temporal differences in water availability per triggering event result in spatially diverse response times varying from 20 to 60 days for rainfall‐triggered events and between 0 and 8 days for events triggered by snowmelt. Pronounced spatio‐temporal differences of snowmelt within the model domain were identified to offer a unique possibility to delineate the effective hydrological landslide catchment. While considering event‐specific time‐lags, logarithmic correlations between incoming water and landslide displacement rate become apparent. Abstract : This contribution presents investigations on the hydrological drivers of the Vögelsberg landslide in Tyrol (Austria). Results obtained from a spatially distributed hydroclimatological model combined with continuous recordings of the landslide movement were analysed in a comprehensive and optimized workflow in order to identify and describe spatio‐temporal patterns of landslide triggering hydro‐meteorological events and to establish time‐delayed relations between landslide displacement rate and incoming water. ​